The Failure and Promise of Mandated Consumer Mortgage Disclosures: Evidence from Qualitative Interviews and a Controlled Experiment with Mortgage Borrowers - Lacko, James M.; Pappalardo, Janis K. (The American economic review, 2010)
The results of this study, based on quantitative testing in a controlled, randomized experiment with more than 800 mortgage borrowers, and in-depth, qualitative interviews with several dozen additional borrowers, suggest that federally mandated consumer mortgage disclosures failed, resulting in many borrowers who did not understand the costs and risks of their loans, likely contributing to the mortgage crisis. Nearly a quarter of the subjects viewing the current disclosures could not correctly identify the amount of settlement charges, about a third could not identify the interest rate, a third did not recognize that the loan included a large balloon payment, a third did not recognize that the loan amount included money borrowed to pay for settlement charges, half could not correctly identify the loan amount, two-thirds did not recognize the fact that they would have to pay a prepayment penalty if they refinanced, three-quarters did not recognize that a substantial charge for optional add-on credit insurance was included in the costs, and nearly nine-tenths could not identify the total amount of up-front charges. Disclosures can be significantly improved. Participants viewing the prototype disclosures answered an average of 80% of the loan term questions correctly, compared to an average of 61% for participants viewing the mandated disclosures. Eighty percent of those viewing the prototype disclosures were able to answer at least 70% of the questions correctly, compared to 29% of those viewing the mandated disclosures.